A novel lipocalin homologue from the venom gland of Deinagkistrodon acutus similar to mammalian lipocalins - Wei,CB (2012)
Lipocalins are involved in a variety of functions including retinol transport, cryptic coloration, olfaction, pheromone transport, prostaglandin synthesis, regulation of the immune response and cell homeostatic mediation. A full-length cDNA clone (named d-lipo), isolated from the venom gland cDNA library of Deinagkistrodon acutus, contained an insert of 664 bp including an open reading frame that encodes a lipocalin homologue of 177 amino acids. Comparison of d-lipo and other related proteins revealed an overall amino acid identity of less than 21.5%. Primary structures of d-lipo carried three structurally conserved regions (SCR) showing homologies to those of lipocalins. The first conserved Cys residue - the essential amino acid residue for the catalytic activity and unique to lipocalin-type prostaglandin D synthase (L-PGDS) in the lipocalin protein family - was identified in d-lipo at amino acid position 58. Phylogenetic tree analysis showed that d-lipo was in-between the large L-PGDS cluster and the small von Ebner's-gland proteins (VEGP) cluster. Moreover, d-lipo gene presented a high-level expression in the venom gland and a low-level expression in the brain and its expression was significantly increased under pathological conditions, suggesting a possible relationship between d-lipo mRNA expression and the venom gland inflammatory disease. This is also the first report of a lipocalin homologous gene identified in the venom gland of a snake.